QED(3) RADIATIVE-CORRECTIONS IN THE HEISENBERG PICTURE - Pimentel, B. M.; Suzuki, A. T.; Tomazelli, J. L. (Plenum Publ Corp, 1994)
We evaluate the vacuum polarization tensor for three-dimensional quantum electrodynamics (QED3) via Heisenberg equations of motion in order to clarify the problem arising from the use of different regularization prescriptions in the interaction picture. We conclude that the photon does acquire physical mass of topological origin when such contribution is taken into account for the photon propagator.